Partial substitution of anthracite for coke breeze in iron ore sintering - Xin Zhang (Nature Portfolio, 2021)
Abstract In the sintering of iron ores, the partial substitution of anthracite for coke breeze has been considered to be an effective way of reducing pollutant emissions and production cost. In this study, the basic characteristics of anthracite and coke breeze were compared and the sintering performance at different substitution ratios of anthracite for coke breeze was investigated. The porosity of anthracite is lower than that of coke breeze, but its density and combustion reactivity are higher. The substitution of anthracite for coke breeze has no influence on the granulation effect of the sintering blend. As the anthracite proportion increased, the sintering speed and productivity increased and the sintering yield and tumbler index decreased. As the substitution ratio increased from 0 to 60%, the melting temperature duration and the melt quantity index decreased from 2.59 to 2.03 min and from 3218.28 to 2405.75 °C·min, respectively, leading to insufficient sintering mineralization and bad sintering indexes. For an anthracite substitution ratio of 40%, the sintering speed, sintering productivity, sintering yield and tumbler index were 22.34 mm min−1, 1.49 t·(m2 h)−1, 71.65% and 63.59%, respectively, which entirely satisfies the production requirements. Furthermore, hematite (Fe2O3), calcium ferrite (CaO–Fe2O3), and compound calcium ferrite (CaO–SiO2–Fe2O3) were the major mineral phases, which were embedded with an interwoven structure.